A case of cryptococcal necrotizing fasciitis and immune reconstitution inflammatory syndrome in a renal transplantation recipient. (August 2021) - Kuwahara, Masamitsu; Yurugi, Satoshi; Ando, Junji; Takeuchi, Mika; Miyata, Riyo; Harada, Masayuki; Masuda, Yasumitsu; Kanagawa, Saori; Yoneda, Tatsuo; Fukumori, Tatsuya; Ogawa, Taku; Nakamura-Uchiyama, Fukumi; et al.
Abstract: Introduction and importance: Immunocompromised patients are at high risk of unexpectedly serious infections caused by uncommon bacteria or fungi. We experienced a case of Cryptococcus neoformans -induced necrotizing fasciitis (NF) of the lower extremities. The progress so far has been reported by the urology department [1] . Moreover, after the NF had been treated, the patient developed immune reconstitution inflammatory syndrome (IRIS). We report from surgeon's view point. Case presentation: A 51-year-old male renal transplant patient complained of pain in both lower extremities (LE). After the initial debridement, periodic acid-Schiff after diastase digestion (D-PAS) staining confirmed the diagnosis. No symptoms were seen in the lungs or cerebrospinal system. The patient was reluctant to undergo surgical treatment but several debridement improved patient's condition. After the LE wound healed, prednisolone was discontinued, then painful nodules appeared on both LE. Based on the negative culture results and the fact that the patient had been treated with flucytosine and fluconazole, we suspected that the nodules had been caused by IRIS. Clinical discussion: It was difficult to diagnose Cryptococcus-induced NF and paradoxical IRIS. Cooperation from other specialists was essential. Conclusion: We think this patient needed earlier and more definitive debridement. Fortunately, we were able to save the patient's life and maintain his LE function. In immunocompromised patients, cryptococcus can be a pathogen. In addition, IRIS can occur during treatment. Management of IRIS is the capital point of sepsis management, careful anti-inflammatory drug control by specialists is required. Highlights: A case of necrotizing fasciitis due to cryptococcosis in both lower extremity of a kidney transplant patient Debridement and systemic drug treatment saved the patient's life. Extensive necrosis of the gastrocnemius tendon was noted. However, we could maintain the patient's lower limb function. The patient also developed immune reconstitution syndrome.